A Prospective Study to Determine the Prevalence of Type 2 Diabetes Mellitus and Hypertension in Cataract Patients at a Tertiary Care Hospital - Malik, Mohammed Abdul Shoeb; Hafsa, Umme Kulsum; Tazeen, Syeda Khadija; Shah, Saifa Mansur; Sharaf, Hannan Ahmed (Indian Journal of Pharmacy Practice)
Objectives: This study was conducted to evaluate the prevalence of hypertension and diabetes mellitus in patients diagnosed with cataract in low-income category. Materials and Methods: The study included 100 cataract patients based on inclusion and exclusion criteria from the Department of ophthalmology, Shadan Institute of medical sciences, Teaching Hospital and Research Centre. During a period of 6 months, patients were assessed based on the following risk factors: diabetes mellitus, hypertension, both or none. Results: Majority of our patients did not have any co-morbidities (34%). Having both hypertension and diabetes (31%) was seen to be a major risk factor for the cataract development as compared to having only hypertension or only diabetes. Female patients seem to be at a slightly higher risk in all age groups. The age group of 45-50 years had the most patients. Conclusion: Female patients seem to be at a slightly higher risk of cataract with and without co morbidity as compared to male patients. The highest prevalence of cataract was reported in the patients suffering from both Hypertension and diabetes which was 31%. Most of the patients belonged to 45-50 years age group. In conclusion, the overall prevalence of hypertension was 25% and that of diabetes mellitus was 10%. Hence, hypertension (25%) seemed to be more prevalent as compared to diabetes mellitus.
Keywords: Cataract; Prevalence; Hypertension; Diabetes mellitus